Hydraulic Conductivity in Relation to Some Physical Characteristics of Soils - Lole, B.S.; Khanvilkar, T; Mishra, V.K. (Journal of Soil and Water Conservation, 2022)
Hydraulic conductivity is closely related to physical characteristics of soils and it is very low due to presence of comparatively large amount of exchangeable sodium in the exchange complex.